Fine workmanship when Al- Bukhari Imam in the multiple hadiths in the one chapter Through (Book of Knowledge) from (Sahih Al- Bukhari) - Kullab, Mohammed Khaled; Abdulghafour, Mohamed Ahmed (Journal of Islamic Sciences, 2020)
The research dealt with a brief translation of Imam Muhammad bin Ismail Al- Bukhari, and revealed his method of referring multiple hadiths in the one section in his Sahih, where Imam Bukhari was distinguished by the mention of hadiths with one subject; Putting a title for it, given under each title a sentence of hadiths, and taking into account in its arrangement a specific purpose for which those hadiths are spoken. The hadith may include the name of the narrator, or an indication of an increase in the narration, or an expression of a statement to hear a narrator from another, a copy of a sentence, an absolute restriction, or an overall detail, Absolute, or detail in detail, or taking into account a chronological history of the novel, to other benefits that we reached in this research, and in which we used the method of deduction and analysis through contemplation of the hadiths he mentioned in the (book of knowledge) from (his Sahih), which was included under fifty- three sections.
Keywords: Al- Bukhari; Al- Sahih; Al- Alam; Al- Matn; Al- Minhaj